Changes in run‐off and sediment load in the three parts of the Yellow River basin, in response to climate change and human activities. Issue 4 (17th December 2018) - Gu, Chaojun; Mu, Xingmin; Gao, Peng; Zhao, Guangju; Sun, Wenyi
Abstract: Hydrological regimes in the Yellow River have changed significantly because of climate change and intensive human interventions. These changes present severe challenges to water resource utilization and ecological development. Variation of run‐off, suspended sediment load (SSL), and eight precipitation indices (P1: 0–12 mm·day −1, P12: 12–25 mm·day −1, P25: 25–50 mm·day −1, P50: P ≥ 50 mm·day −1 and corresponding rainfall day: Pd1, Pd12, Pd25, Pd50 day year −1 ) in three critical parts of the Yellow River basin (source region: SRYRB, upper reaches: URYRB, middle reaches: MRYRB) were investigated for the period from 1960 to 2015. The results show that run‐off and SSL significantly decreased ( P < 0.01) in the URYRB and the MRYRB, whereas their decline in the SRYRB was insignificant ( P > 0.05). Moreover, run‐off in the URYRB had one change point in 1987, and SSL in the URYRB as well as run‐off and SSL in the MRYRB had two change points (in the 1970s and the 1990s). Over the same period, only Pd1 and Pd12 in the SRYRB showed significant increasing trends, and an abrupt change appeared in 1981. The optimal precipitation indices for assessing the effects of precipitation on run‐off and SSL in the URYRB and MRYRB were Pd50 and P12, respectively. A double‐mass curve analysis showed that precipitation and human activities contributed to approximately 20% and 80% of the reduction in run‐off, respectively, for both the SRYRB and the MRYRB. However, the contribution rate of precipitation and human activities on SSL reduction was approximately 40% and 60% in the URYRB and 5% and 95% in the MRYRB, respectively. Human activities, primarily soil and water conservation measures and water extraction (diversion), were the main factors (>50%) that reduced the run‐off. However, the dominant driving factors for SSL reduction were soil and water conservation measures and reservoir interception, for which the contribution rate was higher than 70% in the MRYRB. This work strengthens the understanding of hydrological responses to precipitation change and provides a useful reference for regional water resource utilization.